The Influence of Competency and Career Development on Employee Performance: A Study at Bank BJB Sukajadi Branch Office - Nursiti Nursiti; Nina Nurani (Dinasti Publisher, 2025)
Improving the quality of human resources is inseparable from the role and support of the company's management, because the success or failure of the company's performance is influenced by the performance of employees individually and in groups. The decline in employee performance at Bank BJB Sukajadi Branch Office may be caused by suboptimal career development and insufficient employee competency. The research method is descriptive and verificative, data collection techniques through questionnaires, the research sample is 100 respondents, and using non-probability sampling. The research variables consist of 1 dependent variable (Y) namely employee performance, and 2 independent variables namely career development (X1) and competency (X2). This research was tested using multiple linear regression, coefficient of determination, and hypothesis testing. The results of the study indicate that descriptive results show that career development, competency, and employee performance are relatively low. Meanwhile, verificative results obtained that: 1) career development has a significant effect on employee performance, and 2) competency has a significant effect on employee performance. The magnitude of the influence between career development and competence on the performance of Bank BJB Sukajadi Branch Office employees is 66.7% and the remainder is influenced by other factors not examined in this study.